From Farm to Classroom: Tubers as Key Resources in Developing Biology Learning Media Rooted in Banten's Local Culture - Leksono, S. M.; Kurniasih, S.; Marianingsih, P.; Nuryana, S.; Camara, J. S.; El Islami, R. A. Z.; Cahya, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to investigate the diversity of tuber plants used as food by the people in Banten, which are then used as learning content based on local potential. To achieve this goal, we conducted a research and development (RD) method to create various media using the information of tubers diversity in Banten. In the first stage, we collected data on the diversity of tuber plants cultivated by residents in Banten province and their uses. In the second stage, we developed various forms of learning media from the diversity data and the status of plant utilization. Data on diversity was obtained by conducting field observation and interviews with 373 respondents: tuber farmers, traders, intermediaries, processed makers, souvenir shop owners, and homemakers in Banten. Data were analyzed using the descriptive-qualitative method. Information about the diversity of types of tubers, their use for food, and their processing techniques then use as the content on learning media of Biology subject for senior high school on biodiversity, ecosystems, and biotechnology concept. We customize content development to support Biology classes using the Kurikulum Merdeka. The results showed that there were 16 species of tubers used as food, belong to 11 families, such as Dioscoreaceae, Euphorbiaceae, and Convolvulaceae which used as a staple food, snacks, and vegetables. The results of the media development analysis show that diversity data can be applied to various types of multimedia learning media in the biological sciences. While these materials may complement the learning of Biology, careful consideration must be given to the advantages and disadvantages of each medium to ensure that they are appropriate to the learning goals and circumstances of the learners.